Thermally conductive silicone composition

A thermally conductive silicone composition with specific components addresses the challenge of high thermal conductivity and compressibility for thin silicon chips, ensuring effective heat dissipation and chip protection.

JP7606439B2Active Publication Date: 2024-12-25SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021171220
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-19
Publication Date
2024-12-25
Estimated Expiration
2041-10-19

AI Technical Summary

Technical Problem

Thermally conductive silicone compositions for thin silicon chips face challenges in achieving high thermal conductivity and compressibility without causing damage, as traditional fillers like alumina and aluminum nitride can lead to wear or cracking.

Method used

A thermally conductive silicone composition comprising organopolysiloxanes with specific kinematic viscosity, hydrolyzable organopolysiloxanes, amorphous zinc oxide particles, and a combination of fillers with controlled particle sizes and Mohs hardness, ensuring high thermal conductivity and compressibility while preventing chip damage.

Benefits of technology

The composition achieves appropriate thickness and thermal conductivity, maintaining high heat dissipation performance while minimizing damage to silicon chips, with improved electrical insulation and viscoelastic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606439000001
    Figure 0007606439000001
  • Figure 0007606439000002
    Figure 0007606439000002
  • Figure 0007606439000003
    Figure 0007606439000003
Patent Text Reader

Abstract

To provide a thermally conductive silicone composition which has high thermal conductivity and compressibility to 50 μm or less and causes no damage to a silicon chip.SOLUTION: There is provided a thermally conductive silicone composition which comprises (A) an organopolysiloxane having a kinematic viscosity at 25°C of 10 to 100000 mm2 / s, (B) a hydrolyzable organopolysiloxane having an alkoxysilyl group and (C) a thermally conductive filler in which the content of coarse particles having an average particle diameter of 4 to 30 μm and a particle diameter of 45 μm or more is 0.5 mass% or less of the total component (C) and (D) irregularly shaped zinc oxide particles having an average particle diameter of 0.01 to 2 μm which constitute 1 to 50 mass% of the total composition, wherein the component (C) contains irregularly shaped zinc oxide particles of 40 to 90 mass% of the total composition and the thermally conductive silicone composition has a thermal conductivity of 2.0 W / m K or more and less than 7.0 W / m K and a viscosity of 5 to 800 Pa s at 25°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive silicone composition. [Background technology]

[0002] It is widely known that semiconductor elements generate heat during use and the resulting decrease in performance, and various heat dissipation technologies are used as a means of solving this problem. In general, a cooling member (such as a heat sink) is placed near the heat-generating part, and the two are placed in close contact with each other, and heat is efficiently removed from the cooling member to dissipate heat. In this case, if there is a gap between the heat-generating part and the cooling member, the heat conductivity decreases due to the presence of air with low thermal conductivity, and the temperature of the heat-generating part does not decrease sufficiently. To prevent this phenomenon, heat-dissipating materials with good thermal conductivity and conformability to the surface of the part, such as heat-dissipating grease and heat-dissipating sheets, are used.

[0003] In recent years, the amount of heat generated during operation of high-grade semiconductors, such as server CPUs and insulated gate bipolar transistors (IGBTs) for vehicle drive, is increasing. As the amount of heat generated increases, the heat dissipation performance required for heat dissipation greases and heat dissipation sheets is also improving, and heat dissipation materials using alumina (aluminum oxide), aluminum nitride, etc. as thermally conductive fillers have been proposed (Patent Documents 1 and 2).

[0004] Meanwhile, in recent years, silicon chips have become thinner, and when alumina or aluminum nitride with high Mohs hardness is used as a thermally conductive filler, there is a problem that the chip wears or cracks, so a thermally conductive silicone composition using a filler with low Mohs hardness has been proposed (Patent Document 3). However, when applied to thin films of 50 μm or less, the performance was insufficient. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-210518 A [Patent Document 2] JP 2020-169231 A [Patent Document 3] JP 2020-111655 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and has as its object to provide a thermally conductive silicone composition that has high thermal conductivity and compressibility to 50 μm or less, and that does not damage silicon chips. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides (A) Kinematic viscosity at 25°C is 10 to 100,000 mm 2 / s, (B) a hydrolyzable organopolysiloxane containing an alkoxysilyl group, (C) a thermally conductive filler having an average particle size of 4 μm or more and 30 μm or less, and a content of coarse particles having a particle size of 45 μm or more as measured by a laser diffraction particle size distribution measurement method of 0.5 mass% or less of the total amount of component (C); And, (D) irregular zinc oxide particles with an average particle size of 0.01 μm or more and 2 μm or less A thermally conductive silicone composition comprising: the component (C) contains irregular zinc oxide particles, and the amount of the irregular zinc oxide particles is 40 to 90% by mass of the entire composition; The amount of the component (D) is 1 to 50% by mass of the total composition, The thermal conductivity of the thermally conductive silicone composition, as measured by a hot disk method in accordance with ISO 22007-2, is 2.0 W / m K or more and less than 7.0 W / m K, and The present invention provides a thermally conductive silicone composition having a viscosity of 5 to 800 Pa·s at 25°C and a rotation speed of 10 rpm, as measured with a spiral viscometer.

[0008] This thermally conductive silicone composition has high thermal conductivity and compressibility to 50 μm or less, making it possible to suppress damage to silicon chips.

[0009] Furthermore, in the thermally conductive silicone composition of the present invention, the component (A) is an organopolysiloxane that has one or more aliphatic unsaturated hydrocarbon groups bonded to silicon atoms per molecule, and further (E) an organohydrogenpolysiloxane having two or more hydrogen atoms bonded to silicon atoms in one molecule; (F) a platinum metal catalyst, and (G) Reaction control agent The composition may contain:

[0010] Such a composition has higher thermal conductivity and compressibility to 50 μm or less, and can suppress damage to silicon chips.

[0011] The above-mentioned thermally conductive silicone composition preferably has a tracking resistance of 350 V or greater when measured in a tracking resistance test conforming to JIS C 2134.

[0012] If the tracking resistance is 350 V or greater, the electrical insulation performance of the thermally conductive silicone composition will be even better.

[0013] The thermally conductive silicone composition has a complex elastic modulus G at 10% strain when the composition is 2.0 mm thick, at 120° C., and at an angular velocity of 1 rad / s. * It is preferable that the loss modulus G″ / storage modulus G′ ratio is 8.0 or less.

[0014] By having the viscoelastic properties fall within this range, pumping out of the silicone composition can be suppressed when the substrate expands or vibrates after mounting.

[0015] Furthermore, the thermally conductive silicone composition preferably has a thickness of 5 μm or more and 45 μm or less when a 100 μm thick thermally conductive silicone composition is pressed at 25° C. and 0.1 MPa for 60 minutes.

[0016] If the material has such a thickness after compression, there is no risk of the substrates rubbing against each other when they expand due to heat, and the thermal resistance does not become too high, making it an optimal thermally conductive silicone composition. Effect of the Invention

[0017] According to the present invention, it is possible to obtain a silicone composition which has a suitable thickness and thermal conductivity during practical use, and therefore has high heat dissipation performance, and which is less likely to cause damage to silicon chips. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] As described above, there has been a need for the development of a thermally conductive silicone composition that has high thermal conductivity and compressibility to 50 μm or less, and that will not damage silicon chips.

[0019] As a result of intensive research conducted by the present inventors in order to achieve the above-mentioned object, they discovered that a silicone composition containing an organopolysiloxane having a specific kinetic viscosity, a hydrolyzable organopolysiloxane having alkoxysilyl groups, and irregular zinc oxide particles having a specific particle size has high thermal conductivity and compressibility to 50 μm or less, and is capable of suppressing damage to silicon chips, thereby completing the present invention.

[0020] That is, the present invention provides a composition having a kinetic viscosity of 10 to 100,000 mm at 25°C. 2(B) an organopolysiloxane having a molecular weight of 100 or more and a molecular weight of 100 or more; (C) a thermally conductive filler having an average particle size of 4 μm or more and 30 μm or less, and a content of coarse particles having a particle size of 45 μm or more as measured by a laser diffraction particle size distribution measurement method of 0.5 mass% or less of the total amount of component (C); and (D) amorphous zinc oxide particles having an average particle size of 0.01 μm or more and 2 μm or less, The thermally conductive silicone composition is characterized in that the component (C) contains amorphous zinc oxide particles, the amount of the amorphous zinc oxide particles being 40 to 90 mass% of the total composition, and the amount of the component (D) is 1 to 50 mass% of the total composition, the thermally conductive silicone composition having a thermal conductivity of 2.0 W / m K or more and less than 7.0 W / m K as measured by a hot disk method in accordance with ISO 22007-2, and a viscosity of 5 to 800 Pa s at 25°C and 10 rpm as measured with a spiral viscometer.

[0021] The present invention will be described in detail below, but the present invention is not limited thereto.

[0022] The present invention relates to a thermally conductive silicone composition that has excellent insulating properties and low abrasion properties. The thermally conductive silicone composition of the present invention is characterized by comprising an organopolysiloxane having a specific kinetic viscosity as component (A), a hydrolyzable organopolysiloxane containing an alkoxysilyl group as component (B), a thermally conductive filler having a specific particle size as component (C), and amorphous zinc oxide particles having an average particle size of 0.01 μm or more and 2 μm or less as component (D). As described below, the composition may further comprise other components as necessary. Each component will be described below.

[0023] [Component (A)] Component (A) has a kinetic viscosity of 10 to 100,000 mm at 25°C. 2 / s, preferably 30 to 10,000 mm 2 / s, and more preferably 100 to 8,000 mm 2The organopolysiloxane has a kinematic viscosity of 20 / s. If the kinematic viscosity of the organopolysiloxane is lower than the lower limit, oil bleeding is likely to occur when the organopolysiloxane is made into a silicone composition. If the kinematic viscosity is higher than the upper limit, the silicone composition may have poor extensibility. In the present invention, the kinematic viscosity of the organopolysiloxane is a value at 25°C measured with an Ostwald viscometer.

[0024] In the present invention, the organopolysiloxane may be any organopolysiloxane having the above-mentioned kinetic viscosity, and any known organopolysiloxane may be used. The molecular structure of the organopolysiloxane is not particularly limited, and may be any of linear, branched, and cyclic. In particular, the main chain is preferably a linear structure in which the diorganosiloxane unit is repeated and both ends of the molecular chain are blocked with triorganosiloxy groups. The organopolysiloxane may be used alone or in combination of two or more kinds.

[0025] The organopolysiloxane can be represented, for example, by the following average composition formula (1). R 1 a SiO (4-a) / 2 (1) In the above average composition formula (1), R 1 are each independently a saturated or unsaturated, unsubstituted or substituted monovalent hydrocarbon group having 1 to 18 carbon atoms, preferably 1 to 14. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl, cycloalkyl groups such as cyclopentyl and cyclohexyl, alkenyl groups such as vinyl and allyl, aryl groups such as phenyl and tolyl, aralkyl groups such as 2-phenylethyl and 2-methyl-2-phenylethyl, and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, or with a cyano group, for example, a 3,3,3-trifluoropropyl group, a 2-(perfluorobutyl)ethyl group, a 2-(perfluorooctyl)ethyl group, and a p-chlorophenyl group, and the like are preferred.

[0026] In the above average composition formula (1), a is a number within the range of 1.8 to 2.2, and particularly within the range of 1.9 to 2.1. By having a within the above range, the obtained silicone composition can have a good viscosity.

[0027] As the organopolysiloxane represented by the above average composition formula (1), a linear organopolysiloxane represented by the following formula (2) is preferred. [ka]

[0028] In the above formula, R 2 are each independently a saturated or unsaturated, unsubstituted or substituted monovalent hydrocarbon group having 1 to 18 carbon atoms, preferably 1 to 14 carbon atoms. As the monovalent hydrocarbon group, R 1 In addition, at least one R 2 is preferably a vinyl group. m is a value that indicates that the kinetic viscosity of the organopolysiloxane at 25° C. is 10 to 100,000 mm 2 / s, preferably 30 to 10,000 mm 2 / s, and more preferably 100 to 8,000 mm 2 / s.

[0029] The blending amount of component (A), in terms of the total of component (A) and component (B) described below, is preferably 1 to 50 mass % of the thermally conductive silicone composition, and more preferably 3 to 10 mass %. By including components (A) and (B) in this range, it is possible to prevent deterioration of thermal resistance due to oil separation and pump-out while maintaining good compressibility. Component (A) may be blended alone or in combination of two or more types. When blending in combination of two or more types, it is preferable that each of the organopolysiloxanes has a kinetic viscosity at 25°C of 10 to 100,000 mm 2 / s, and the entire component (A) may have the above kinematic viscosity.

[0030] [(B) Component] The (B) component is a hydrolyzable organopolysiloxane having an alkoxysilyl group. The (B) component acts as a thermally conductive filler of the (C) component and a surface treatment agent of the (D) component, which will be described later. Therefore, the addition of the (B) component strengthens the interaction between the (A) component and the (C) and (D) components. As a result, even if the (C) component is filled with a large amount of the thermally conductive filler and the (D) component, the thermally conductive silicone composition can maintain its fluidity. At the same time, the deterioration of heat dissipation performance caused by oil separation and pump-out over time can be suppressed. Examples of the (B) component include organopolysiloxanes represented by the following general formula (3). Among them, it is preferable to contain a trifunctional hydrolyzable organopolysiloxane.

[0031] [ka] (In the formula, R 3 X is independently an unsubstituted or substituted monovalent hydrocarbon group. 1 , X 2 , X 3 is R 3 Or -(R 4 ) n -SiR 5 d (OR 6 ) 3-d may be different, but at least one of them is -(R 4 ) n -SiR 5 d (OR 6 ) 3-d R 4 is an oxygen atom or an alkylene group having 1 to 4 carbon atoms, R 5 are independently unsubstituted or substituted monovalent hydrocarbon groups containing no aliphatic unsaturated bonds, R 6 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group or an acyl group having 1 to 4 carbon atoms, n is 0 or 1, and d is an integer of 0 to 2. b and c are 1≦b≦1,000 and 0≦c≦1,000, respectively.

[0032] In the above formula (3), R 3are independently unsubstituted or substituted monovalent hydrocarbon groups having preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, and even more preferably 1 to 3 carbon atoms, examples of which include linear alkyl groups, branched alkyl groups, cyclic alkyl groups, alkenyl groups, aryl groups, aralkyl groups, halogenated alkyl groups, and the like. Examples of linear alkyl groups include methyl groups, ethyl groups, propyl groups, hexyl groups, and octyl groups. Examples of branched alkyl groups include isopropyl groups, isobutyl groups, tert-butyl groups, and 2-ethylhexyl groups. Examples of cyclic alkyl groups include cyclopentyl groups and cyclohexyl groups. Examples of alkenyl groups include vinyl groups and allyl groups. Examples of aryl groups include phenyl groups and tolyl groups. Examples of aralkyl groups include 2-phenylethyl groups and 2-methyl-2-phenylethyl groups. Examples of halogenated alkyl groups include a 3,3,3-trifluoropropyl group, a 2-(nonafluorobutyl)ethyl group, and a 2-(heptadecafluorooctyl)ethyl group. 3 As the alkyl group, a methyl group, a phenyl group, and a vinyl group are preferred.

[0033] R 4 Examples of the alkylene group having 1 to 4 carbon atoms include a methylene group, an ethylene group, a propylene group, and a butylene group. 5are independently unsubstituted or substituted monovalent hydrocarbon groups not containing an aliphatic unsaturated bond, preferably having 1 to 10 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3. Examples include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl groups, cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl groups, aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenylyl groups, aralkyl groups such as benzyl, phenylethyl, phenylpropyl, and methylbenzyl groups, and groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine, or with cyano groups, etc.

[0034] Above R 6 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group having 1 to 4 carbon atoms. 6 Examples of the alkyl group include R 3 Examples of the alkoxyalkyl group include a methoxyethyl group and a methoxypropyl group. Examples of the alkenyl group include a vinyl group and an allyl group. 6 The acyl group of R is preferably one having 2 to 8 carbon atoms, and examples of the acyl group include an acetyl group and an octanoyl group. 6 is preferably an alkyl group, and particularly preferably a methyl group or an ethyl group.

[0035] b and c are as described above, but preferably b+c is 10 to 1,000, more preferably 10 to 300. n is 0 or 1, and d is an integer of 0 to 2, preferably 0. In addition, if OR 6 The number of groups is preferably 1 to 6, and more preferably 3 or 6. The bonding order of the siloxane units shown in parentheses is not particularly limited.

[0036] Specific examples of suitable components (B) include, but are not limited to, the following: [ka]

[0037] The blending amount of the (B) component relative to the (A) component is preferably in the range of (A):(B)=1:99 to 50:50 (mass ratio), more preferably in the range of 5:95 to 20:80. The (B) component may be blended either alone or in combination of two or more.

[0038] [(C) component] Component (C) is a thermally conductive filler with an average particle size of 4 μm to 30 μm, preferably 5 μm to 25 μm. If the average particle size of component (C) is less than 4 μm, the thermal conductivity of the thermally conductive silicone decreases. If it is greater than 30 μm, it is technically difficult to reduce the amount of coarse particles with a particle size of 45 μm or more contained in component (C). As a result, the thermally conductive silicone composition cannot be made into a thin film, and sufficient heat dissipation performance cannot be achieved.

[0039] The average particle size is the cumulative average diameter D 50 (median diameter) and can be measured, for example, by Microtrac MT330OEX manufactured by Nikkiso Co., Ltd.

[0040] The content of coarse particles having a particle size of 45 μm or more in component (C) is 0.5% by mass or less of the total amount of component (C), and preferably 0 to 0.3% by mass. If the content of the coarse particles exceeds 0.5% by mass, the thermally conductive silicone composition cannot be compressed to a thickness of 50 μm or less, and sufficient heat dissipation performance cannot be achieved. The particle size is a volume-based value measured by a laser diffraction scattering method.

[0041] The content of the coarse particles can be measured, for example, by the above-mentioned Microtrac MT330OEX manufactured by Nikkiso Co., Ltd.

[0042] The thermally conductive silicone composition of the present invention contains amorphous zinc oxide particles as a thermally conductive filler. Zinc oxide has a Mohs hardness of 4, which is softer than silicon (Mohs hardness 7) that is generally used in semiconductors, and therefore does not wear down the tip. The Mohs hardness referred to here is sometimes written as the old Mohs hardness, and is an index that expresses hardness on a scale of 10, with the hardest diamond having a hardness of 10.

[0043] The thermally conductive silicone composition of the present invention contains 40 to 90 mass% of amorphous zinc oxide particles as the thermally conductive filler of component (C) relative to the entire composition. If the content of the amorphous zinc oxide particles in component (C) is less than 40 mass%, the thermal conductivity of the thermally conductive silicone composition decreases, and if it exceeds 90 mass%, the thermally conductive silicone composition will not be uniform.

[0044] Thermally conductive fillers other than amorphous zinc oxide particles are not particularly limited, but examples include hexagonal boron nitride (2), which is softer than silicon (7), magnesium hydroxide (2.5), anhydrous magnesium carbonate (3.5), magnesium oxide (6), fused silica (6), etc. Aluminum nitride (7), silicon nitride (8), aluminum oxide (9), etc. are as hard as silicon or harder, but may be included to the extent that they do not damage the silicon chip. In addition, the shapes of these are also not particularly limited. Note that the numbers in parentheses above are Mohs hardness.

[0045] When two or more types of thermally conductive fillers are used in combination, each of the thermally conductive fillers must have an average particle size of 4 μm or more and 30 μm or less, and the content of coarse particles having a particle size of 45 μm or more as measured by a laser diffraction particle size distribution measurement method must be 0.5 mass% or less of the total component (C), and the above conditions may be satisfied for component (C) as a whole.

[0046] [(D) component] Component (D) is amorphous zinc oxide particles with an average particle size of 0.01 μm or more and 2 μm or less, preferably 0.05 μm or more and 1.5 μm or less. Component (D) can improve the filling property by combining with the above-mentioned thermally conductive filler (component (C)) which has a larger average particle size. Component (D) itself has thermal conductivity, so that in combination with the improved filling property, the thermal conductivity can also be improved. If the average particle size of component (D) is less than 0.01 μm, the viscosity of the thermally conductive silicone composition increases significantly, and if it is more than 2 μm, the thermally conductive silicone composition will not be uniform.

[0047] The average particle size is the cumulative average diameter D 50 (median diameter) and can be measured, for example, by Microtrac MT330OEX manufactured by Nikkiso Co., Ltd.

[0048] The blending amount of component (D) is 1 to 50 mass% of the entire thermally conductive silicone composition of the present invention, and preferably 20 to 40 mass%. If the blending amount of component (D) is less than 1 mass%, the thermally conductive silicone composition will not be homogeneous, and if it exceeds 50 mass%, the viscosity of the thermally conductive silicone composition will increase significantly.

[0049] When the thermally conductive silicone composition of the present invention is an organosiloxane in which component (A) above contains one or more aliphatic unsaturated hydrocarbon groups per molecule, the thermally conductive silicone composition can be made into an addition reaction type thermally conductive silicone composition by further adding components (E) to (G) below.

[0050] [(E) component] Component (E) is an organohydrogenpolysiloxane having two or more, and preferably at least 3 but less than 40, hydrogen atoms bonded to silicon atoms (SiH groups) per molecule, and the silicon-bonded hydrogen atoms in the molecule undergo an addition reaction with aliphatic unsaturated hydrocarbon groups in the composition in the presence of a platinum group metal catalyst described below to form a crosslinked structure.

[0051] There are no particular limitations on the molecular structure of component (E) and it may be, for example, linear, branched, or cyclic, and those represented by the average composition formula below can be used. R 7 e H f SiO (4-e-f) / 2

[0052] In the formula, R 7 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 18 carbon atoms, preferably 1 to 14 carbon atoms, excluding aliphatic unsaturated hydrocarbon groups. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl, cycloalkyl groups such as cyclopentyl and cyclohexyl, alkenyl groups such as vinyl and allyl, aryl groups such as phenyl and tolyl, aralkyl groups such as 2-phenylethyl and 2-methyl-2-phenylethyl, and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, or cyano groups, such as 3,3,3-trifluoropropyl, 2-(perfluorobutyl)ethyl, 2-(perfluorooctyl)ethyl, and p-chlorophenyl. 7 As the alkyl group, a methyl group and a phenyl group are particularly preferred. e is a positive number of 1.0 to 3.0, preferably 0.5 to 2.5, f is 0.005 to 2.0, preferably 0.01 to 1.0, and e+f is a positive number of 0.5 to 3.0, preferably 0.8 to 2.5.

[0053] The amount of component (E) to be blended is preferably an amount such that the number of hydrogen atoms bonded to silicon atoms in component (E) per aliphatic unsaturated hydrocarbon group bonded to silicon atoms in component (A) is 0.1 to 5.0, more preferably 0.1 to 1.0. Within such a range, crosslinking is sufficient and the composition is easy to handle. Also, component (E) may be blended alone or in combination of two or more.

[0054] [Component (F)] Component (F) is a platinum group metal catalyst, which is a catalyst for promoting the hydrosilylation reaction between an aliphatic unsaturated hydrocarbon group such as an alkenyl group in component (A) and a SiH group in component (E). The platinum group metal catalyst may be any of those conventionally known for use in addition reactions. Examples include platinum-based, palladium-based, and rhodium-based catalysts, of which platinum or platinum compounds, which are relatively easy to obtain, are preferred. Examples include platinum alone, platinum black, chloroplatinic acid, platinum-olefin complexes, platinum-alcohol complexes, and platinum coordination compounds.

[0055] The amount of component (F) added is preferably within the range of 1 to 2,000 ppm, and more preferably 2 to 1,000 ppm, calculated as the mass of platinum group metal atoms relative to the organopolysiloxane of component (A), which ensures an appropriate reaction rate for the addition reaction. The component (F) may be used alone or in combination of two or more types.

[0056] [(G) component] The (G) component is a reaction inhibitor that suppresses the progress of the hydrosilylation reaction at room temperature, and functions to extend shelf life and pot life. The inhibitor can be a conventional inhibitor used in addition curing silicone compositions. Examples of the inhibitor include acetylene compounds such as acetylene alcohols (e.g., ethynylmethyldecylcarbinol, 1-ethynyl-1-cyclohexanol, 3,5-dimethyl-1-hexyn-3-ol), various nitrogen compounds such as tributylamine, tetramethylethylenediamine, benzotriazole, and oxime compounds, organic phosphorus compounds such as triphenylphosphine, and organic chloro compounds.

[0057] [Other ingredients] The thermally conductive silicone composition of the present invention may contain a non-reactive organo(poly)siloxane such as methylpolysiloxane for the purpose of adjusting the elastic modulus and viscosity. In addition, in order to prevent deterioration of the silicone composition, a known antioxidant such as 2,6-di-t-butyl-4-methylphenol may be contained as necessary. Furthermore, dyes, pigments, flame retardants, anti-settling agents, thixotropy improvers, etc. may be blended as necessary.

[0058] [Thermal conductive silicone composition] The thermal conductivity of the thermally conductive silicone composition of the present invention, as measured by the hot disk method in accordance with ISO 22007-2, is equal to or greater than 2.0 W / m K and less than 7.0 W / m K. As will be described later, the thermal conductivity can be measured by wrapping the thermally conductive silicone composition in kitchen wrap, forming a test piece into a pouch, and measuring the thermal conductivity at 25°C using a TPA-501 manufactured by Kyoto Electronics Manufacturing Co., Ltd.

[0059] The thermally conductive silicone composition of the present invention has a viscosity of 5 to 800 Pa·s, preferably 10 to 500 Pa·s, at 25°C and 10 rpm, as measured by a spiral viscometer. If the viscosity is less than 5 Pa·s, workability may be impaired, such as difficulty in maintaining the shape. If the viscosity exceeds 800 Pa·s, workability may be impaired, such as difficulty in discharging. The viscosity can be adjusted by blending the above-mentioned components. In the present invention, the viscosity (absolute viscosity) is a value measured using a spiral viscometer at 10 rpm and 25°C.

[0060] The thermally conductive silicone composition of the present invention preferably has a tracking resistance of 350 V or greater when measured in a tracking resistance test conforming to JIS C 2134.

[0061] The viscoelastic properties of the thermally conductive silicone composition of the present invention are as follows: complex modulus G at 10% strain, when the composition is 2.0 mm thick, at 120°C, and at an angular velocity of 1 rad / s. *It is preferable that the viscoelasticity is 10,000 Pa s or less, and the value of loss modulus G" / storage modulus G' is 8.0 or less. Having the viscoelasticity properties in this range makes it possible to prevent pumping-out of the silicone composition when the substrate expands or vibrates after mounting. The viscoelasticity properties are measured as described below, by using a viscoelasticity measuring device to apply a thermally conductive silicone composition to a thickness of 2.0 mm between two specified parallel plates, raising the temperature from 25°C at a rate of 5°C / min, and then maintaining the temperature at 120°C for 10 minutes. After that, the strain is increased while shearing at an angular velocity of 1 rad / s to measure the storage modulus G', loss modulus G", complex modulus G * It is sufficient to measure the above.

[0062] The thermally conductive silicone composition of the present invention has good compressibility. When the thermally conductive silicone composition having a thickness of 100 μm is subjected to a pressure of 25° C. and 0.1 MPa for 60 minutes, the thickness of the thermally conductive silicone composition is preferably 5 μm or more and 45 μm or less, more preferably 10 μm or more and 32 μm or less. If the thickness is such, there is no risk of the substrates rubbing against each other when they expand due to heat, and the thermal resistance does not become too large, so it is optimal as a thermally conductive material. Note that, as described below, the method of measuring the thickness when pressure is applied is to sandwich a thermally conductive silicone composition having a thickness of 100 μm between two predetermined circular aluminum plates, apply pressure at 25° C. and 0.1 MPa for 60 minutes, measure the thickness of the test piece obtained with a micrometer, and measure the thickness of the composition after pressure by subtracting the thickness of the aluminum plates.

[0063] The thermally conductive silicone composition of the present invention is optimal as a thermally conductive silicone composition because zinc oxide with low Mohs hardness is used as a filler. It does not wear out when rubbed against a silicon chip. The test method for the abrasion test is the same as the silicon chip scratch test described below, in which a test piece is obtained by sandwiching a thermally conductive silicone composition between two silicon wafers and applying pressure at 25°C and 0.1 MPa for 60 minutes, and then manually rubbing two silicon wafers facing each other through the thermally conductive silicone composition 100 times at 1 time / second, and then washing the wafers with a toluene solution and observing the surfaces with an optical microscope.

[0064] The thermally conductive silicone composition of the present invention can be advantageously used for dissipating heat by interposing it between an LSI or other electronic component or other heat-generating component and a cooling component, and can be used in the same manner as conventional heat-conductive silicone greases.

[0065] [Method of producing thermally conductive silicone composition] The method for producing the thermally conductive silicone composition of the present invention will now be described, but is not limited to this.

[0066] The method for producing the thermally conductive silicone composition of the present invention may be according to the conventional method for producing a thermally conductive silicone composition, and is not particularly limited. For example, the composition can be obtained by mixing the above-mentioned components (A) to (D), and, if necessary, (E), (F), (G) and other optional components. The mixing device is not particularly limited, and mixers such as Trimix, Twinmix, Planetary Mixer (all registered trademarks of mixers manufactured by Inoue Seisakusho Co., Ltd.), Ultra Mixer (registered trademarks of mixers manufactured by Mizuho Kogyo Co., Ltd.), and Hivis Dispermix (registered trademarks of mixers manufactured by Tokushu Kika Kogyo Co., Ltd.) can be used. In addition, a three-roll finishing treatment or the like may be performed to break down the agglomerations of the amorphous zinc oxide particles of the components (C) and (D) which are thermally conductive fillers.

[0067] When component (A) is an organopolysiloxane having one or more aliphatic unsaturated hydrocarbon groups bonded to silicon atoms per molecule, and the above-mentioned components (E), (F), and (G) are used, it is preferable to mix them for at least 30 minutes at a temperature of 100°C or higher. This allows components (A) and (E) to sufficiently crosslink via a hydrosilylation reaction, and allows the thermally conductive silicone composition to have a more appropriate viscosity. EXAMPLES

[0068] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following, the kinematic viscosity is a value measured at 25°C using an Ostwald viscometer (manufactured by Shibata Scientific Co., Ltd.).

[0069] The components used were as follows: [Component (A)] A-1: Both ends are blocked with dimethylvinylsilyl groups, and the kinetic viscosity at 25°C is 600mm 2 / s Dimethylpolysiloxane

[0070] [(B) Component] B-1: Hydrolyzable organopolysiloxane represented by the following formula: [ka]

[0071] [(C) component] C-1:D 50 Irregular zinc oxide powder with a particle size of 5.0 μm (Mohs hardness: 4, coarse particles of 45 μm or more: less than 0.1 mass%) C-2:D 50 Irregular zinc oxide powder with a particle size of 11.0 μm (Mohs hardness: 4, coarse particles of 45 μm or more: less than 0.1 mass%) C-3:D 50 Irregular zinc oxide powder with a particle size of 21.0 μm (Mohs hardness: 4, coarse particles of 45 μm or more: 0.4 mass%) C-4:D 50Spherical zinc oxide powder with a particle size of 20.0 μm (Mohs hardness: 4, coarse particles of 45 μm or more: 1.9% by mass) C-5:D 50 Polyhedral alumina powder with a particle size of 3.5 μm (Mohs hardness: 9, coarse particles of 45 μm or more: less than 0.1 mass%)

[0072] [(D) component] D-1:D 50 Irregular zinc oxide powder with a diameter of 1.3 μm (Mohs hardness: 4) D-2:D 50 Irregular zinc oxide powder with a particle size of 0.4 μm (Mohs hardness: 4) D-3:D 50 Amorphous aluminum nitride with a grain size of 0.7 μm: (Mohs hardness: 8) D-4:D 50 Amorphous alumina with a diameter of 1.4 μm (Mohs hardness: 9)

[0073] [(E) component] E-1: Both ends are blocked with trimethylsilyl groups, and the kinetic viscosity at 25°C is 100mm 2 / s and the SiH group content is 0.0055 mol / g.

[0074] [Component (F)] F-1: A solution of platinum-divinyltetramethyldisiloxane complex dissolved in the same dimethylpolysiloxane as A-1 (platinum atom content: 1% by mass)

[0075] [(G) component] G-1: Ethynylcyclohexanol

[0076] [Examples 1 to 6, Comparative Examples 1 to 6] Preparation of Thermally Conductive Silicone Composition The above components (A) to (G) were blended in the amounts shown in Tables 1 and 2 below, and by the method shown in the Preparation Example below, to prepare a silicone composition.

[0077] (Preparation Example) Components (A) to (G) were added to a 5 liter planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.) and mixed for 3 hours at 150° C. After that, the mixture was cooled to 25° C. to prepare a silicone composition.

[0078] The compositions obtained by the above methods were evaluated for viscosity, thermal conductivity, thickness, viscoelasticity, damage to silicon chips, and tracking resistance according to the following methods. The results are shown in Tables 1 and 2.

[0079] <Evaluation> [viscosity] The absolute viscosity of the thermally conductive silicone composition was measured using a spiral viscometer (Type PC-1T, Rotor A) manufactured by Malcom Corporation at 25° C., a rotation speed of 10 rpm, and a shear rate of 6 [1 / s].

[0080] [Thermal Conductivity] The thermally conductive silicone composition was wrapped in kitchen wrap and made into a drawstring bag-shaped test piece, and the thermal conductivity of the test piece was measured at 25°C using a TPA-501 manufactured by Kyoto Electronics Manufacturing Co., Ltd.

[0081] Thickness A 100 μm thick thermally conductive silicone composition was sandwiched between two circular aluminum plates, each 12.6 mm in diameter and 1 mm thick, and pressure was applied for 60 minutes at 25° C. and 0.1 MPa to prepare a test piece. The thickness of the test piece was measured with a micrometer (manufactured by Mitutoyo Corporation), and the thickness of the aluminum plates was subtracted to measure the thickness of the composition after pressure.

[0082] [Viscoelasticity] The thermally conductive silicone composition was applied to a thickness of 2.0 mm between two parallel plates with a diameter of 2.5 cm. The temperature of the applied plate was raised from 25°C at a rate of 5°C / min, and then the temperature was maintained at 120°C for 10 minutes. After that, the plate was sheared at an angular velocity of 1.0 rad / s while increasing the strain to measure the storage modulus G', loss modulus G'', complex modulus G * The measurements were performed using a viscoelasticity measuring device (TA Instruments, Type ARES-G2). *The loss modulus G″ / storage modulus G′ value is the value at 10% strain.

[0083] [Silicon chip damage test] A test piece was prepared by sandwiching a 100μm thick thermally conductive silicone composition between two 10mm square silicon wafers and applying pressure at 25℃ and 0.1MPa for 60 minutes. The two silicon wafers facing each other through the thermally conductive silicone composition were manually rubbed 100 times at 1 time / second, and then the wafers were washed with a toluene solution and the wafer surfaces were observed under an optical microscope. If there were no scratches, they were marked ◯, and if scratches were observed, they were marked ×.

[0084] [Tracking resistance test] The composition was applied at 25°C and 50% RH to a thickness of 3 mm and a square of 1.3 cm to prepare a test piece. Using a Yamayo Tester YST-112 model, both ends were clamped with electrodes, and 0.1% aqueous ammonium chloride solution was dripped onto the test piece while applying a voltage of 350 V. If the test piece was not destroyed after 50 drops were dripped, it was marked as ◯, and if it was destroyed, it was marked as ×. The above was performed in accordance with JIS C 2134.

[0085] [Table 1]

[0086] [Table 2] In the above Tables 1 and 2, "mass fraction of amorphous zinc oxide (C)" is the mass fraction of amorphous zinc oxide particles contained in the thermally conductive filler of component (C) relative to the entire composition.

[0087] The results in Tables 1 and 2 show that the thermally conductive silicone compositions of Examples 1 to 6, which satisfy the requirements of the present invention, have high thermal conductivity and good compressibility, while also preventing damage to silicon chips.

[0088] On the other hand, in Comparative Example 1, which does not contain the component (C) of the present invention, the thermal conductivity was insufficient, and furthermore, the silicon chip was damaged. In Comparative Example 2, in which a composition having a content of coarse particles of 45 μm or more in the component (C) was used that exceeded the range of the present invention, the thickness was 80 μm, and the heat dissipation performance was insufficient. In Comparative Example 3, in which alumina having a high Mohs hardness was used instead of the component (C) of the present invention, and in Comparative Examples 4 and 5, in which alumina having a high Mohs hardness or aluminum nitride was used instead of the component (D) of the present invention, the silicon chip was damaged. In Comparative Example 6, in which a composition having a viscosity of more than 800 Pa·s was used, the composition was unable to follow the displacement of the chip during the scratching test and fell off, resulting in damage to the silicon chip.

[0089] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. (A) A kinematic viscosity at 25°C of 10 to 100,000 mm 2 / s, a linear organopolysiloxane having one or more aliphatic unsaturated hydrocarbon groups bonded to silicon atoms in one molecule, represented by the following formula (2): 【Chemistry 1】 (In the formula, R 2 s are each independently a saturated or unsaturated, unsubstituted or substituted monovalent hydrocarbon group having 1 to 18 carbon atoms, and m is a number that causes the kinematic viscosity of the linear organopolysiloxane at 25° C. to be in the above-mentioned numerical range.) (B) a hydrolyzable organopolysiloxane containing an alkoxysilyl group, (C) a thermally conductive filler having an average particle size of 4 μm or more and 30 μm or less, and a content of coarse particles having a particle size of 45 μm or more as measured by a laser diffraction particle size distribution measurement method of 0.5 mass% or less of the total amount of component (C); (D) irregular zinc oxide particles having an average particle size of 0.01 μm or more and 2 μm or less; (E) an organohydrogenpolysiloxane having two or more hydrogen atoms bonded to silicon atoms in each molecule; (F) Platinum metal catalyst and (G) Reaction control agent A thermally conductive silicone composition comprising: The component (C) contains amorphous zinc oxide particles, and the amount of the amorphous zinc oxide particles is 40 to 90 mass% of the total composition, The amount of the component (D) is 1 to 50% by mass of the total composition, the amount of component (E) is such that the number of hydrogen atoms bonded to silicon atoms in component (E) per one aliphatic unsaturated hydrocarbon group bonded to silicon atoms in component (A) is 0.1 to 1.5, The thermal conductivity of the thermally conductive silicone composition, as measured by a hot disk method in accordance with ISO 22007-2, is 2.0 W / m K or more and less than 7.0 W / m K, and A thermally conductive silicone composition having a viscosity of 5 to 800 Pa·s at 25° C. and 10 rpm as measured by a spiral viscometer.

2. The component (A) is a linear organopolysiloxane represented by the formula (2), in which at least one R 2 is a vinyl group, 2. The thermally conductive silicone composition according to claim 1, wherein the component (B) is contained in a ratio of component (A):component (B) in the range of 5:95 to 20:

80.

3. 3. The thermally conductive silicone composition according to claim 1, which has a tracking resistance of 350 V or greater when measured in a tracking resistance test conforming to JIS C 2134.

4. Complex elastic modulus G at 10% strain under conditions of 2.0 mm thickness, 120°C, and angular velocity of 1 rad / s * 4. The thermally conductive silicone composition according to claim 1, wherein the viscosity of the composition is 10,000 Pa s or less, and the value of loss modulus G" / storage modulus G' is 8.0 or less.

5. 5. The thermally conductive silicone composition according to claim 1, wherein when a thermally conductive silicone composition having a thickness of 100 μm is pressed at 25° C. and 0.1 MPa for 60 minutes, the thickness of the silicone composition is 5 μm or more and 45 μm or less.

Citation Information

Patent Citations

  • Liquid silicone rubber composition for high-voltage insulation part and its production

    JP1998212414A

  • Silicone grease composition for heat dissipation, and semiconductor device using the same

    JP2000109373A

  • Thermally conductive silicone composition and cured product of the same

    JP2017210518A

  • Thermal conductive silicone composition and production method thereof

    JP2020063365A

  • Heat conductive silicone composition

    JP2020111655A